Modulation of Atopy Patch Test and Skin Prick Test by Pretreatment with 1% Pimecrolimus Cream - Weissenbacher, Stephanie; Traidl-Hoffmann, Claudia; Eyerich, Kilian; Katzer, Kerstin; Braeutigam, Matthias; Loeffler, Helena; Hofmann, Heidelore; Behrendt, Heidrun; Ring, Johannes; Darsow, Ulf (International Archives of Allergy and Immunology, 2006)
Background: In a subgroup of patients with atopic eczema (AE), aeroallergens are relevant eliciting factors. The atopy patch test (APT) was proposed as inflammation model for AE. Objective: It was the aim of this study to investigate the effect of pretreatment with 1% pimecrolimus cream (Elidel ® ) on the APT and skin prick test (SPT). Methods: In a randomized, controlled, double-blind study, 20 patients with AE and positive SPT and APT screening reaction to house dust mite Dermatophagoides pteronyssinus, cat dander, grass or birch pollen were enrolled (age 20 ± 11 years, 55% males). For 2 weeks, patients twice daily applied pimecrolimus and vehicle control to marked fields on their backs and forearms. Then, APT was performed (200 index of reactivity/g extracts in petrolatum; Stallergènes, France) on both fields on the back and SPT was performed on the pretreated forearms. Results: Including only patients with different readings (n = 13), stronger APT suppression of at least 1 ETFAD (European Task Force on Atopic Dermatitis) grade in the pimecrolimus area versus intraindividual control was observed in 10 of these patients after 48 and 72 h (p < 0.05; 90% CI 50.5–93.4). Including all 20 subjects, the analysis still showed a borderline significance compared with the vehicle (p = 0.0564). SPT with histamine and aeroallergens showed a median 7.5–10% reduction in actively pretreated areas (p = 0.086). Immunohistochemical analysis in 2 patients revealed an induction of interferon-γ in primecrolimus-pretreated skin. Conclusion: APT can be used as a model for AE skin inflammation. It was shown for the first time that pimecrolimus pretreatment has a potential to suppress the development of lesions induced by aeroallergen exposure in patients with AE.